Clinical and Brain Magnetic Resonance Imaging Features in a Cohort of Chinese Patients with Kearns-Sayre Syndrome - Yu, Meng (Chin Med J (Engl), 2016)
BACKGROUND: Kearns-Sayre syndrome (KSS) is a mitochondrial DNA (mtDNA) deletion disorder characterized by a triad of onset before 20 years of age, ophthalmoplegia, and pigmentary retinopathy. The heart and central nervous system are commonly involved. We summarized clinical and brain magnetic resonance imaging (MRI) features of a cohort of Chinese KSS patients. METHODS: Nineteen patients confirmed by muscle biopsy and mtDNA analysis were enrolled. We examined clinical profiles, mainly focusing on changes in electrocardiogram (ECG) and brain MRI. The correlation between genotype and phenotype was statistically analyzed. RESULTS: The mean age of onset was 9.6 ± 4.3 years, with all developing the classic triad at the time of diagnosis. Heart conduction block was detected in 63.2%, with four initially presenting as bundle branch block and developing into complete atrioventricular block over 3–72 months. Brain MRI showed symmetric high-T2 signals in 100% of cerebral and cerebellar white matter, as well as brainstem, 46.7% of basal ganglia, and 53.3% of thalamus. There were two patterns of cerebral white matter involvements, one with selective subcortical U-fibers and the other with periventricular white matter. The size of mtDNA deletion did not significantly correlate with age of onset or percentage of ragged blue fibers on muscle pathology. CONCLUSIONS: The clinical features of KSS evolve dynamically, affecting the cardiac conduction system predominantly, highlighting the significance of ECG monitoring. Brain MRI showed changes involving both the white matter and deep gray nuclei. Clinical presentation or severity of muscle pathological changes is not related to the size of mtDNA deletions.